Konsep Konsep Kecerdasan Majemuk Dalam Psikologi dan Implikasinya Terhadap Teori Pembelajaran PAI - Nisa, Ummu Khairin; Idris, Husni (Prodi Pendidikan Keagamaan Islam, 2025)
Creating learning strategies that cater to students' diverse intelligences has become an urgent priority within Islamic Religious Education (PAI), especially in light of modern educational demands. This article examines the psychological framework of multiple intelligences, particularly focusing on Howard Gardner’s theory, and evaluates its significance for instructional strategies in PAI. Utilizing a qualitative approach through a literature review, this study references primary sources, including Gardner’s seminal works and academic journals, alongside secondary sources such as scholarly books and pertinent articles. The findings suggest that implementing the multiple intelligences framework in PAI can promote a more comprehensive and inclusive educational approach. In this regard, PAI educators play a crucial role as facilitators who adapt teaching methods to align with the diverse intelligence profiles of students, which encompass linguistic, logical-mathematical, kinesthetic, musical, emotional, and spiritual intelligences. The article concludes that employing a strategy informed by multiple intelligences enhances the effectiveness and contextual relevance of Islamic education and upholds its fundamental humanistic values. Future research involving qualitative fieldwork is suggested to evaluate these strategies' practical application and effects in actual classroom environments.